Biomimicry – Core Stages, Design Process, and Gaps - Toong Foo, Chin; Omar, Badrul; Jalil, Azlis-Sani (International Journal of Engineering and Technology, 2019)
Nature is a world-scale R&D in a laboratory called the universe. Some of the best inventions and innovations are actually built based on nature’s design. But in order to wield the power of nature’s design, one must first learn about the three core stages of biomimicry: Search, Abstract, and Transfer. One must also know the steps of designing with biomimicry, either problem-driven or solution-based design process. Since Theory of Inventive Principles (TRIZ) is known as the most promising tool to bridge the biology-engineering gap, this paper presented both problem-driven and solution based design process with TRIZ cycle. There had been many biomimicry tools emerging since 1987, but tuning and refinements are still required. The biology-engineering gap is still far from being bridged. This paper presented some of the ideas of potential approaches in bridging the biology-engineering gap; TRIZ, Function-Behaviour-Structure (FBS) modelling, and pattern language.